Fatal massive and recurring pulmonary embolism followed by thrombocytopenia developed after heparin and warfarin treatment in a patient with metastatic breast cancer with an incidental large right atrial thrombus. Issue 2 (March 2016) - Cho, Young Kyu; Park, Byoung-won; Lee, Min Ho; Hyon, Min Su; Bang, Duk Won; Kim, Yong Jae
Abstract : A thromboembolic complication such as pulmonary embolism in patients who had cancer and mobile thrombi in the heart is a rare but fatal complication. Surgical thromboembolectomy is considered as the classical treatment of choice. In case of inoperable patient, catheter-directed therapy may be an alternative treatment. We report an interesting case of metastatic breast cancer with a large and mobile right atrial thrombus complicated by a massive and subsequently recurring pulmonary embolism, followed by thrombocytopenia developed after heparin and warfarin treatment.